1996
DOI: 10.1159/000134154
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic patterns of seven species of molossid bats (Molossidae, Chiroptera)

Abstract: G- and C- banding patterns of seven species of the bat family Molossidae, Eumops glaucinus, E. perotis, Molossops abrasus, M. temminckii, Molossus ater, M. molossus, and Nyctinomops laticaudatus, were identified. Comparisons among the karyotypes of these species showed extensive homologies between E. perotis, M. ater, M. molossus, M. abrasus, and N. laticaudatus, demonstrating inter- and intrageneric conservatism, and a lesser degree of homologies in M. temminckii and E. glaucinus, reflecting intrageneric vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 4 publications
(9 reference statements)
6
28
1
Order By: Relevance
“…Comparisons of chromosome banding patterns support the hypothesis that Robertsonian and tandem chromosomal fusions were the main events in the karyotype evolution of Chiroptera, and the reduced chromosomal number found in some species of phyllostomid and molossid bats may have resulted from such events (Morielle-Versute et al, 1996;de Faria and Morielle-Versute, 2006;Ao et al, 2006Ao et al, , 2007Mao et al, 2008).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Comparisons of chromosome banding patterns support the hypothesis that Robertsonian and tandem chromosomal fusions were the main events in the karyotype evolution of Chiroptera, and the reduced chromosomal number found in some species of phyllostomid and molossid bats may have resulted from such events (Morielle-Versute et al, 1996;de Faria and Morielle-Versute, 2006;Ao et al, 2006Ao et al, , 2007Mao et al, 2008).…”
supporting
confidence: 61%
“…Cynomops abrasus and Eumops auripendulus exhibit a smaller number of chromosomes, with 2n = 34 (FN = 64) and 2n = 42 (FN = 62), respectively (Warner et al, 1974;Morielle-Versute et al, 1996). Warner et al (1974) suggested that 48 could be the ancestral diploid number for this family, since 23 species and eight genera show 2n = 48.…”
mentioning
confidence: 99%
“…The karyotypes of E. glaucinus and C. perspicillata have many rearrangements, as compared to karyotypes considered primitive. Only some elements considered primitive are observed in the karyotype of E. glaucinus (Morielle-Versute et al, 1996), whereas in C. perspicillata no primitive karyotypes were identified (Stock, 1975). These observations and the FISH results of C. perspicillata indicate that other chromosomal mechanisms besides telomeric associations are likely to be involved where telomeric hybridization is absent.…”
Section: Discussionmentioning
confidence: 63%
“…This variation ranges from one pair of NORs as observed in Diaemus youngii and Desmodus rotundus, up to five pairs in different species of Myotis (Volleth 1987;Morielle and Varella-Garcia, 1988;Souza and Araújo, 1990;Baker et al, 1992;Morielle-Versute et al, 1996). Moreover, the NORs occur both in terminal regions and interstitial regions of chromosome arms, and they generally correspond to the secondary constrictions.…”
Section: Nucleolus Organizer Regions and Nucleolar Behaviormentioning
confidence: 93%